Impact of water physicochemical properties on the survival of Oncomelania hupensis snails, the intermediate host of Schistosoma japonicum - Yun Feng; Maomao Liu; Liang Shi; Xinyao Wang; Chunrong Xiong; Kun Yang (BMC Infectious Diseases)
Abstract Background Schistosoma japonicum, the causative agent of schistosomiasis, heavily relies on its single intermediate host, the Oncomelania hupensis snail, for its life cycle. Controlling these snails effectively plays a pivotal role in curbing the transmission and prevalence of this disease. While prior research has extensively investigated the impact of environmental factors such as temperature and vegetation on snail survival, growth, and reproduction, the contribution of water physicochemical properties has been notably underexplored. This study presents laboratory experiments designed to comprehensively explore the influence of water physicochemical properties on snail survival, offering valuable insights into environmental factors for more precise predictions of snail distribution. Methods We meticulously conducted laboratory snail survival experiments using water from different sources (river water/tap water), and employed a statistical approach amalgamating principal component analysis with Cox regression to preliminarily investigate the effects of different water physicochemical properties on the survival of snails. Results Our analysis indicates that after a 6-month laboratory snail survival experiment, the survival rate in the tap water group was significantly higher than that in the river water group for infected snails (χ2 = 7.74, p = 0.005), while the difference in survival rates for non-infected snails was not statistically significant (χ2 = 0.61, p = 0.434). The Principal Component-Cox regression analysis revealed that in the infected snail group, total phosphorus, pH value, five-day biochemical oxygen demand, conductivity, and nitrite were protective factors for snail survival, while phosphate and total nitrogen were risk factors. In the non-infected snail group, total phosphorus, pH value, five-day biochemical oxygen demand, conductivity, and nitrite were protective factors for snail survival, and total nitrogen, ammonia nitrogen, phosphate, and nitrate were risk factors. Conclusions This study underscores the substantial impact of water quality’s physicochemical properties on snail survival. The effects of water quality on snails are complex, and maintaining an appropriate level of organic matter content and controlling the pH value at a weak alkalescency level prove beneficial for snail survival. These findings hold significant promise for advancing our understanding of snail-borne diseases and optimizing control strategies.